2008
DOI: 10.1021/tx800213b
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Intracellular Concentrations of Reactive Nitrogen Species

Abstract: Reactive nitrogen species derived from NO have been implicated in cancer and other diseases, but their intracellular concentrations are largely unknown. To estimate them under steady-state conditions representative of inflamed tissues, a kinetic model was developed that included the effects of cellular antioxidants, amino acids, proteins, and lipids. For an NO concentration of 1 µM, total peroxynitrite (Per, the sum of ONOO− and ONOOH), NO2·, and N2O3 were calculated to have concentrations in the nM, pM, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 63 publications
4
75
1
Order By: Relevance
“…COMT assay: The activity assay buffer was 100 mM sodium phosphate at pH 7.6 and 1.2 mM MgCl 2 . The assay mixture contained 1 mM SAM with varying concentrations 3,4-dihydroxybenzoic acid (DHBA) (5,10,15,20,40,60 or 100 µM) and was pre-incubated for 2-3 min at 37 °C before enzyme addition. The assay was initiated by the addition of 200 nM COMT in a 450 µL Eppendorf tube and incubated at 37 °C.…”
Section: Pgd Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…COMT assay: The activity assay buffer was 100 mM sodium phosphate at pH 7.6 and 1.2 mM MgCl 2 . The assay mixture contained 1 mM SAM with varying concentrations 3,4-dihydroxybenzoic acid (DHBA) (5,10,15,20,40,60 or 100 µM) and was pre-incubated for 2-3 min at 37 °C before enzyme addition. The assay was initiated by the addition of 200 nM COMT in a 450 µL Eppendorf tube and incubated at 37 °C.…”
Section: Pgd Assaymentioning
confidence: 99%
“…GSNO stock concentrations were measured before use (ε 335 nm = 0.992 mM -1 cm -1 ). All proteins, except PHGDH, were incubated separately at 20 µM with varying GSNO or GSH concentrations (20,50, 100, 150, 200, 500, 1000 or 2000 µM) at 37 °C for 1 h. PHGDH was incubated at 150 µM with GSNO or GSH concentrations of 150, 500, 1000 or 2000 µM for 1 h. For kinetics experiments, 6PGD and PHGDH were incubated with 2 mM GSH or GSNO for 1 h at 37 ˚C, ALDH4A1, ALDOA, and TPI1 were incubated with 1 mM GSH or GSNO for 1 h at 37˚C and COMT was incubated for 150 µM GSH or GSNO for 1 h at 37 ˚C. Proteins were spun at ~21,000 rcf for 1 min to remove precipitation and the supernatant was buffer exchanged into the appropriate activity buffer using Bio-Spin6 columns.…”
mentioning
confidence: 99%
“…Kinetic models integrating these reactions with the formation of other RNS have shown that N 2 O 3 formation would not be very important at the NO concentrations estimated for biological systems (82,87).…”
Section: Nonenzymatic Biochemistry Of S-nitrosylation Formationmentioning
confidence: 99%
“…NO reacts with superoxide anion (O 2 −• ) at diffusion-controlled rates to yield highly reactive peroxynitrite (ONOO − ) (26,27). MPO also reacts H 2 O 2 with nitrite (NO 2 − , the endpoint of cellular NO oxidation) to produce the strong nitrating agent, nitrogen dioxide radical (NO 2 • ) (28).…”
mentioning
confidence: 99%